2009
DOI: 10.1111/j.1460-9568.2009.06967.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing and anticipation: conceptual and methodological approaches

Abstract: Anticipation occurs on timescales ranging from milliseconds to hours to days. This paper relates the theoretical and methodological developments in the study of interval timing in the seconds, minutes and hours range to research on the anticipatory activity induced by regularly timed daily meals. Daily food anticipatory activity (FAA) is entrained by procedures which are formally identical to procedures studied in Pavlovian and Operant conditioning except for the long duration of the interval between feeding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 68 publications
(76 reference statements)
1
53
0
Order By: Relevance
“…It has been suggested that anticipatory operant behaviors may emerge at an earlier point in the intermeal interval than wheel-running or general locomotor behavior, making operant behaviors a more sensitive measure of anticipatory activity in feeding schedules with meals provided at intervals of less than 24 hr (Balsam et al, 2009;Crystal, 2001aCrystal, , 2006aCrystal, , 2006b. Although this proposal is arguably counterintuitive (animals must first awaken before they can start working for food), we nonetheless sought evidence to substantiate the idea that apparent limits to antic ipation might depend on the behavioral measures.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that anticipatory operant behaviors may emerge at an earlier point in the intermeal interval than wheel-running or general locomotor behavior, making operant behaviors a more sensitive measure of anticipatory activity in feeding schedules with meals provided at intervals of less than 24 hr (Balsam et al, 2009;Crystal, 2001aCrystal, , 2006aCrystal, , 2006b. Although this proposal is arguably counterintuitive (animals must first awaken before they can start working for food), we nonetheless sought evidence to substantiate the idea that apparent limits to antic ipation might depend on the behavioral measures.…”
Section: Discussionmentioning
confidence: 99%
“…In the unfed control of our study on the postprandial changes in SPX gene expression, transient drops in basal levels of SPX transcript were also noted in the hypothalamus and optic tectum during the scheduled feeding period. These may be related to the food-anticipatory responses commonly reported in entrained animals (2). In goldfish with proper entrainment, NPY mRNA levels could be upregulated in brain areas, including diencephalon and hypothalamus, during the meal time without food administration (21).…”
Section: E363 Structure and Function Of Goldfish Spexinmentioning
confidence: 93%
“…The existence of a feedingentrainable clock does not exclude the participation of memory processing (e.g. conditioning; Balsam et al 2009) and hourglass mechanisms (e.g. depletion of glycogen stores; Mistlberger 2009) in food anticipation.…”
Section: Effects Of Meal-associated Reward On Extra-scn Cerebral Clocmentioning
confidence: 99%